Difficult relationships: critical pedagogies and curriculum - Di Caudo Villoslada, María Verónica (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper reviews the proposals of the ‘critical pedagogies’ and presents some difficulties in the realization of their principles in the context of current public policies in Latin America. Distances between discourses and practices, absence of radically democratic educational policies, lack of awareness of critical pedagogies by teachers, lack of contextual production and indiscriminate use of the word critical—that ends up opposing everything that is considered as traditional pedagogy—makes us wonder about the real possibility of transformation in order to fight against the dominant power relationships through counter-hegemonic and destabilizing practices in education.